Performance Accountability of the Civil Service Police Unit in Regulating Billboards in Sukabumi City - Intan Quraeni Nursomantri; Yana Fajar FY Basori; Dine Meigawati (Prediksi : Jurnal Administrasi dan Kebijakan, 2026)
The proliferation of unlicensed billboards and their placement in violation of regulations in the city of Sukabumi indicates a gap between policy and its implementation on the ground. This study aims to analyze the performance accountability of the Sukabumi City Civil Service Police Unit in regulating advertisements using Koppell’s (2005) theory of accountability, which includes transparency, liability, control, responsibility, and responsiveness. This study employs a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and document analysis, validated through triangulation of sources and methods. The results indicate that the performance accountability of the Civil Service Police Unit is in place, but there are still several aspects that need improvement to ensure more optimal implementation. In the transparency dimension, information dissemination has been supported by the use of digital communication and reporting systems, although the disclosure of information to the public still needs to be expanded. In the liability dimension, material accountability mechanisms have functioned well but are not yet accompanied by an effective formal system of rewards and sanctions. The controllability dimension is still hampered by the lack of measurable performance targets and inter-agency data integration. In the responsibility dimension, enforcement activities have been supported by compliance with applicable procedures and regulations. Meanwhile, the responsiveness dimension remains limited due to the public’s low utilization of complaint channels. Strengthening the performance accountability of the Civil Service Police Unit can be achieved by establishing measurable enforcement performance targets, developing a formal system of rewards and sanctions for officers, expanding public awareness of complaint channels and extending patrol coverage to the entire city; and strengthening inter-agency data integration, accompanied by stricter administrative sanctions for repeat offenders.